Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Claro, vamos a resolver la expresión paso a paso.
Primero, sabemos que [tex]\( r = \sqrt{2} + 1 \)[/tex]. Queremos encontrar el valor de la expresión [tex]\( r^2 - 2r - 2 \)[/tex].
### Paso 1: Calcula [tex]\( r^2 \)[/tex]
Dado que [tex]\( r = \sqrt{2} + 1 \)[/tex]:
[tex]\[ r^2 = (\sqrt{2} + 1)^2 \][/tex]
Usamos el cuadrado de un binomio:
[tex]\[ r^2 = (\sqrt{2})^2 + 2 \cdot (\sqrt{2}) \cdot 1 + 1^2 \][/tex]
[tex]\[ r^2 = 2 + 2\sqrt{2} + 1 \][/tex]
[tex]\[ r^2 = 3 + 2\sqrt{2} \][/tex]
### Paso 2: Calcula [tex]\(-2r\)[/tex]
Dado que [tex]\( r = \sqrt{2} + 1 \)[/tex]:
[tex]\[ -2r = -2(\sqrt{2} + 1) \][/tex]
[tex]\[ -2r = -2\sqrt{2} - 2 \][/tex]
### Paso 3: Sustituye los valores calculados en la expresión original
Ahora sustituimos [tex]\( r^2 \)[/tex] y [tex]\(-2r\)[/tex] en la expresión [tex]\( r^2 - 2r - 2 \)[/tex]:
[tex]\[ r^2 - 2r - 2 = (3 + 2\sqrt{2}) + (-2\sqrt{2} - 2) - 2 \][/tex]
Primero sumamos y restamos los términos:
[tex]\[ r^2 - 2r - 2 = 3 + 2\sqrt{2} - 2\sqrt{2} - 2 - 2 \][/tex]
Observamos que [tex]\( 2\sqrt{2} \)[/tex] y [tex]\(-2\sqrt{2} \)[/tex] se cancelan entre sí:
[tex]\[ r^2 - 2r - 2 = 3 - 2 - 2 \][/tex]
Finalmente, realizamos la resta:
[tex]\[ r^2 - 2r - 2 = 3 - 4 \][/tex]
[tex]\[ r^2 - 2r - 2 = -1 \][/tex]
Por lo tanto, el valor de la expresión [tex]\( r^2 - 2r - 2 \)[/tex] cuando [tex]\( r = \sqrt{2} + 1 \)[/tex] es [tex]\(-1\)[/tex].
Primero, sabemos que [tex]\( r = \sqrt{2} + 1 \)[/tex]. Queremos encontrar el valor de la expresión [tex]\( r^2 - 2r - 2 \)[/tex].
### Paso 1: Calcula [tex]\( r^2 \)[/tex]
Dado que [tex]\( r = \sqrt{2} + 1 \)[/tex]:
[tex]\[ r^2 = (\sqrt{2} + 1)^2 \][/tex]
Usamos el cuadrado de un binomio:
[tex]\[ r^2 = (\sqrt{2})^2 + 2 \cdot (\sqrt{2}) \cdot 1 + 1^2 \][/tex]
[tex]\[ r^2 = 2 + 2\sqrt{2} + 1 \][/tex]
[tex]\[ r^2 = 3 + 2\sqrt{2} \][/tex]
### Paso 2: Calcula [tex]\(-2r\)[/tex]
Dado que [tex]\( r = \sqrt{2} + 1 \)[/tex]:
[tex]\[ -2r = -2(\sqrt{2} + 1) \][/tex]
[tex]\[ -2r = -2\sqrt{2} - 2 \][/tex]
### Paso 3: Sustituye los valores calculados en la expresión original
Ahora sustituimos [tex]\( r^2 \)[/tex] y [tex]\(-2r\)[/tex] en la expresión [tex]\( r^2 - 2r - 2 \)[/tex]:
[tex]\[ r^2 - 2r - 2 = (3 + 2\sqrt{2}) + (-2\sqrt{2} - 2) - 2 \][/tex]
Primero sumamos y restamos los términos:
[tex]\[ r^2 - 2r - 2 = 3 + 2\sqrt{2} - 2\sqrt{2} - 2 - 2 \][/tex]
Observamos que [tex]\( 2\sqrt{2} \)[/tex] y [tex]\(-2\sqrt{2} \)[/tex] se cancelan entre sí:
[tex]\[ r^2 - 2r - 2 = 3 - 2 - 2 \][/tex]
Finalmente, realizamos la resta:
[tex]\[ r^2 - 2r - 2 = 3 - 4 \][/tex]
[tex]\[ r^2 - 2r - 2 = -1 \][/tex]
Por lo tanto, el valor de la expresión [tex]\( r^2 - 2r - 2 \)[/tex] cuando [tex]\( r = \sqrt{2} + 1 \)[/tex] es [tex]\(-1\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.